2019
DOI: 10.3389/fimmu.2019.00353
|View full text |Cite
|
Sign up to set email alerts
|

Effector Functions of CD4+ T Cells at the Site of Local Autoimmune Inflammation—Lessons From Rheumatoid Arthritis

Abstract: Infiltration of memory CD4+ T cells in synovial joints of Rheumatoid Arthritis (RA) patients has been reported since decades. Moreover, several genome wide association studies (GWAS) pinpointing a key genetic association between the HLA-DR locus and RA have led to the generally agreed hypothesis that CD4+ T cells are directly implicated in the disease. Still, RA is a heterogeneous disease and much effort has been made to understand its different facets. T cell differentiation is driven by mechanisms including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 205 publications
(216 reference statements)
4
140
0
Order By: Relevance
“…These findings may partly account for the autoimmunity against mesenchymal cell-specific antigens and are relevant to IFN-c-abundant conditions in RA synovium which have already been discussed in the previous section. A number of studies have so far indicated IFNc-secreting CD4þ T cells (Th1 subtype), whose differentiation is also promoted by IFN-c, as effector cells in RA [35]. A skewing towards T cells with a Th1 cytokine profile including IFN-c was observed in synovial fluids from RA patients [36].…”
Section: Ifn-c In Autoimmunitymentioning
confidence: 99%
“…These findings may partly account for the autoimmunity against mesenchymal cell-specific antigens and are relevant to IFN-c-abundant conditions in RA synovium which have already been discussed in the previous section. A number of studies have so far indicated IFNc-secreting CD4þ T cells (Th1 subtype), whose differentiation is also promoted by IFN-c, as effector cells in RA [35]. A skewing towards T cells with a Th1 cytokine profile including IFN-c was observed in synovial fluids from RA patients [36].…”
Section: Ifn-c In Autoimmunitymentioning
confidence: 99%
“…Activated T cells migrating to the synovium locally interact with resident macrophages, dendritic cells, synoviocytes, and osteoclasts. Here, several T cell subsets and their complex interactions likely contribute to RA pathology (reviewed in [37]).…”
Section: Joint Inflammation In Ra Is Mediated By T Cells B Cells Mamentioning
confidence: 99%
“…Via their secretion of IL-2, IFN-γ, and TNF-β, Th1 cells potently provide help to other immune cells, resulting in the activation of macrophages and B cells, thereby initiating and perpetuating inflammatory responses in the synovium [37][38][39]. In addition to their helper function in RA inflammation, CD4 + CD28 null cells co-expressing perforin and granzymes, molecules more commonly found in CD8 + cytotoxic T cells, were recently shown to be increased in peripheral blood of a subset of RA patients [40][41][42].…”
Section: Joint Inflammation In Ra Is Mediated By T Cells B Cells Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages can also be subdivided into pro-inflammatory M1 and anti-inflammatory M2 macrophages, that are characterized by the production of the pro-inflammatory cytokines TNF-alpha, IL-6, IL-12, IL-18, and IL-23, and of the anti-inflammatory cytokine IL-10, respectively [9,10]. Both preclinical and clinical evidence coming from rodent models of RA and RA patients indicate that the CD4+T cell belonging to the Th1 and Th17 subsets, along with M1 macrophages, play a key role in the development and maintenance of RA, as opposed to anti-inflammatory Th2 and Th3 cells, and M2 macrophages that seem to play a protective role on the course of the disease [11].…”
Section: Introductionmentioning
confidence: 99%